2012
DOI: 10.1007/s10761-012-0173-2
|View full text |Cite
|
Sign up to set email alerts
|

Presentation is Everything: Foodways, Tablewares, and Colonial Identity at Presidio Los Adaes

Abstract: Ceramics and zooarchaeological remains are commonly used as indicators of status and wealth at colonial-period sites, yet colonial expectations with regard to cuisine were often difficult to meet within the rigors of frontier life. In this paper, we juxtapose faunal and ceramic assemblages from Presidio Los Adaes and, informed by ethnohistorical and visual data, investigate how social expectations with regard to foodways were negotiated on the Spanish colonial frontier. While ceramic evidence suggests that tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Social rank may also impact dietary patterns. Officers at the Spanish Presidio Los Adaes (Pavao-Zuckerman and Loren 2012) and the US Fort Laramie (Wolff 2016) had greater access to hunting and wild game than lower-ranked soldiers. Interestingly, our study identified no statistically significant differences between officers and soldiers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social rank may also impact dietary patterns. Officers at the Spanish Presidio Los Adaes (Pavao-Zuckerman and Loren 2012) and the US Fort Laramie (Wolff 2016) had greater access to hunting and wild game than lower-ranked soldiers. Interestingly, our study identified no statistically significant differences between officers and soldiers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of Euro-American diet have employed cookbooks and other sources to identify differences in historical diets and define which species were or were not consumed by individuals of a particular ethnicity (Deagan 1973; Pavao-Zuckerman and Loren 2012; Smith-Lintner 2007). The large quantity of sites and diversity of researchers’ reporting standards meant that this more detailed, butchery-focused approach could not be attempted, although we did exclude commensal species and those generally not used as subsistence resources (mice, voles, cats, dogs, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Often, artifacts are classified as either non-local or local, and utilitarian or domestic objects are treated as tools and not objects with deeper significance. The manufacture, use, and style of ceramics are often analyzed using a practice theory framework although researchers vary in their opinions on whether these elements were conscious or unconscious decisions made by migrants (Burmeister, 2000; Croucher and Wynne-Jones, 2006; Naum, 2015; Pavao-Zuckerman and DiPaolo Loren, 2012).…”
Section: Studying Migrants and Their Materials Culturementioning
confidence: 99%
“…To address these critiques, other archaeologists turned to data from skeletal analyses, architecture, and material culture to argue migration events are visible in the archaeological record (Anthony, 1990; Burmeister, 2000; Herr and Clark, 1997; Kulisheck, 2003; Naum, 2015; Stone, 2003) and that the lives of migrants in their new homes can be studied (Faust, 2015; Ryden, 2018; Skiles and Clark, 2010). Emphasis is placed on objects that can be linked with practices associated with maintaining and displaying an individual’s or groups’ identity that are key to the creative adaptability of migrating people (Croucher and Wynne-Jones, 2006; Pavao-Zuckerman and DiPaolo Loren, 2012). Given new data on past migrations, scholars are shifting to examine the meaning and significance of these belongings (Brighton, 2009; Crowell, 2011; De León, 2013, 2015; Faust, 2015; Naum, 2015; Ryden, 2018; Van Oyen and Pitts, 2017).…”
Section: Introductionmentioning
confidence: 99%